All-arround looking antenna based on linear expanding symmetric slot lines - V.P. Zaiarny; E.I. Nefyodov; V.A. Neganov; I.N. Ponomarev; S.A. Parpula; S.V. Girich; V.S. Girich (Физика волновых процессов и радиотехнические системы, 2019)
Properties of the all-arround looking antenna executed on a basis of radiators in the form of linearly expanding slot lines placed on two coaxially located disks displaced azimuthal on a corner are described. The antenna works in the frequency range of (812)GHz, is intended for forming of the directional radiation providing the circular or sector scan.